The impact of posttraumatic stress symptoms, posttraumatic stress cognitions and interpersonal dependency on psychological co-morbidities following relationship dissolution among college students. (3rd September 2018) - Fang, Siqi; Chung, Man Cheung; Watson, Clare
Abstract: Background : Relationship dissolution is a distressing experience which can result in the emergence of posttraumatic stress (i.e. post-dissolution PTSS) and other psychological symptoms among college students. Little is known, however, whether posttraumatic stress cognitions and interpersonal dependency may influence the severity of these distress outcomes. Aims : This study examined the interrelationship between posttraumatic stress symptoms (PTSS), posttraumatic stress cognitions, interpersonal dependency and psychological co-morbidities following relationship dissolution. Methods: One hundred and eighty college students ( M = 69, F = 111) who had experienced relationship dissolution completed the Posttraumatic Stress Diagnostic Scale, Posttraumatic Stress Cognition Inventory, Interpersonal Dependency Inventory and General Health Questionnaire-28. Results : Posttraumatic stress symptoms following relationship dissolution (post-dissolution PTSS) were associated with increased psychological co-morbidities. Negative view of oneself and self-blame mediated between PTSS and psychological co-morbidities. Assertion of autonomy moderated the mediational effects of negative cognitions on psychological co-morbidities. Conclusions : People can develop PTSSs and other psychological symptoms following the dissolution of a romantic relationship. Their concept of self and tendency to seek independence and control played a key role in determining the severity of distress symptoms.